(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
The essay focuses on the interconnections between the processing of genetic data and the goals of scientific research studies. After an analysis of the research exemptions set out by the GDPR to foster researchers’ activities, which are performed by using specifically genetic data, particular attention is shown for the regulatory measures (both public and private) in order to increase data sharing and secondary use of personal data. In this sense, it is essential to move from a perspective closely related to the data subjects towards a governance model led by the data controllers and at the same time overseen by supervisory authorities and ethics committees.